1967
DOI: 10.3758/bf03330734
|View full text |Cite
|
Sign up to set email alerts
|

Trace conditioning with X-rays as an aversive stimulus

Abstract: An aversion to saccharin flavored water (.1%) was conditioned in male albino rats using X-rays as the noxious stimulus. The time interval between CS (saccharin) and US (X-ray) was varied for different groups and it was noted that an aversion could be formed when these stimuli were separated by as much as 12 h. Additional groups were run with 4% sucrose as the CS and the maximum effective time interval between CS and US was approximately 6 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
102
1
1

Year Published

1969
1969
1999
1999

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(109 citation statements)
references
References 7 publications
5
102
1
1
Order By: Relevance
“…For instance, a rat that experiences gastrointestinal illness once after tasting a distinctively flavored fluid will subsequently avoid that fluid (Smith & Roll, 1967). In contrast, Pavlovian conditioning procedures employing appetitive unconditioned stimuli have not yielded evidence of such rapid learning.…”
Section: University Of Texas Austin Texasmentioning
confidence: 99%
“…For instance, a rat that experiences gastrointestinal illness once after tasting a distinctively flavored fluid will subsequently avoid that fluid (Smith & Roll, 1967). In contrast, Pavlovian conditioning procedures employing appetitive unconditioned stimuli have not yielded evidence of such rapid learning.…”
Section: University Of Texas Austin Texasmentioning
confidence: 99%
“…However, the conditions under which learning occurs with a taste CS and an internal aversive UCS seem different from those under which Pavlovian conditioning ordinarily occurs. Aversions have been produced with only a few pairings and with delays between CS and UCS of as long as 6 h or 12 h {Revusky, 1968; Smith & Roll, 1967).…”
mentioning
confidence: 99%
“…With saccharin. this is true even if the interval between ingestion and exposure is extended up to 12 h (Smith & Roll, 1967). Furthermore, it has been shown that rats will form an aversion to saccharin solution when the solution is consumed up to 12 h after exposure to radiation ceases (Scarborough, Whaley, & Rogers, 1964).…”
mentioning
confidence: 85%